2017
DOI: 10.4094/chnr.2017.23.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Development and Effects of a Child Health Management Program Based on Cooperative Learning for Mothers of Preschool Children

Abstract: This study was conducted to develop and test effects of a child health management program based on cooperative learning for mothers of preschool children. Methods: For this quasi-experimental study, a nonequivalent control group pretest-posttest design was used. Outcome measures were level of child health management self-efficacy, child health management practices, child's health behavior. Participants were 55 mothers (experimental group 28, control group 27). The program was composed of 6 categories of home h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In particular, this study result cannot rule out the possibility that data collection was made at the time of the pandemic. In addition, we can assume that the factors affecting the health promotion behaviors were out of control, as various factors can affect health promotion behavior, such as self-efficacy, stress, parental attachment, and epidemic environmental factors [ 9 , 27 ]. Thus, future studies are required that consider the various variables affecting the progress of health behavior in COVID-19 situations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, this study result cannot rule out the possibility that data collection was made at the time of the pandemic. In addition, we can assume that the factors affecting the health promotion behaviors were out of control, as various factors can affect health promotion behavior, such as self-efficacy, stress, parental attachment, and epidemic environmental factors [ 9 , 27 ]. Thus, future studies are required that consider the various variables affecting the progress of health behavior in COVID-19 situations.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, young children aged 1–6 have relatively weak immunity and are less capable of coping with external infectious agents than adults. Moreover, they are especially prone to breathing difficulties and have a very high risk of respiratory disease [ 9 , 10 ]. Based on the above fact, young children are susceptible to both infection and reinfection with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that various types of distraction methods have meaningful effects, reducing children's distress during a needle procedure 1,4–6 . In particular, non‐pharmacologic distraction methods using objects familiar to children, such as toys, dolls, and electronic devices, are widely used in PEDs 7–9 …”
mentioning
confidence: 99%
“…In children, COVID-19— an infectious respiratory disease characterized by variable symptoms including severe respiratory difficulty with cough, fatigue, and shortness of breath ( KDCA, 2021 )—has a much higher propagation power and transmission rate than the previous epidemics, SARS and MERS ( Van Chan et al, 2021 ). Respiratory difficulties are more likely in early childhood (1–6 years old) due to the anatomical narrowing of the airways and young children are highly susceptible to infection as their immune systems are not fully developed ( Lee et al, 2017 ; Park et al, 2011 ; Wong et al, 2001 ). This is driving many people, including young children and parents, into physical and psychological fear of contracting COVID-19 ( Jung, 2020 ; Van Chan et al, 2021 ).…”
mentioning
confidence: 99%